Interfacial Properties of Parrafin Oil Ã¢â‚¬â€ Alcohol Mixture in the Presence ff Glycolipids: Comparison of Interfacial Properties of Glycolipids with the Interfacial Properties of Brij 35P and SDS - Kok Chun, Tham; Boris B, Niraula; Misran, Misni; Kurupiah, Nadarajah (Malaysian Journal of Science, 2003)
The interfacial tension of water and a mixture containing paraffin oil, hexanol and isopropyl alcohol (IPA) was examined as a function of alcohol volume fractions. The interfacial tension aqueous glycolipid solutions, dodecyl glucose ester (obtained from SIRIM) and dodecyl glucose pyranoside, and paraffin oil-alcohol mixture was also examined and compared with the effect of aqueous solutions of Brij 35P and sodium dodecyl sulphate (SDS) on the interfacial behaviors of paraffin-alcohol mixture. The droplet size of the mixture (oil light phase) was measured with the help of spinning drop tensiometer and the measurement of density difference between the heavy and light phases was determined using a densitometer. The interfacial tension between oil and alcohol phases gradually decreased with the increase in alcohol volume fractions, reaching a saturation interfacial tension value of 1.1 mN mÃ¢ÂÂ»Ã‚Â¹ at which the alcohol volume fraction reached 0.35. As far as effect of surfactant on interfacial tension is concerned, depending upon the oil to alcohol mixing ratio and type of surfactant used the interfacial tension that is being developed between the aqueous and oil phases decreased in a various degree. As opposed to other surfactants examined here Dodecyl-ÃƒÅ¸-D-Glucopyranoside (DOP) displayed exceptionally good surface activity, by being effective at all paraffin oil-alcohol mixing ratio. In its presence the interfacial tension of the equal volume fractions of these two liquids decreased from 1.2 mN mÃ¢ÂÂ»Ã‚Â¹ to 0.1 mN mÃ¢ÂÂ»Ã‚Â¹. On the contrary, SIRIM made glucose ester displayed good surface activity only at higher paraffin oil volume fractions, above 0.7. As far as optimal working volume fractions is concerned DGP, Brij 35P and SDS exhibited maximum surface activity at oil volume fractions from 0.5 to 0.70. These volume fractions corresponded to minimum interfacial tension between paraffin oil and IPA-hexanol mixture.